CORRELATION DYNAMICS OF ERRORS AND COMPLICATIONS IN THE USE OF RESTORATIVE POST CONSTRUCTIONS - Ortikova Nargiza Khairullaevna (Web of Journals Publishing, 2024)
Restoration of dental hard tissue defects is one of the actual problems of orthopedic dentistry. Restoration of destroyed teeth using endocanal posts has always been one of the fundamental problems of dentistry. The choice of the type and determination of the number of posts depends on the volume and patency of the canal after endodontic treatment, the number of root canals, the loss of dentin mass, the distance to antagonist teeth and neighboring teeth.
Keywords: Restorative post constructions, restoration of dental hard, endocanal posts, complications in the restoration, dental crown.